Ready, set, yellow! color preference of Indian free-ranging dogs - Anamitra Roy; Aesha Lahiri; Srijaya Nandi; Aayush Manchalwar; S. Siddharth; J. V. R. Abishek; Indira Bulhan; Shouvanik Sengupta; Sandeep Kumar; Tushnim Chakravarty; Anindita Bhadra (Animal Cognition)
Abstract Most of the research on color vision related behaviors in dogs has involved training the dogs to perform visual discrimination tasks. We investigated the importance of color to untrained Indian free-ranging dogs (FRDs). Using one-time multi-option choice tests for color preference in 134 adult dogs, we found the dogs to prefer yellow objects over blue or gray ones while there was no preference between blue and gray. We next pitted a yellow object against a gray object that had food. Here, the dogs ignored the food (biscuit or chicken) to approach the yellow object first indicating the color preference to be quite strong. Color preference has previously been investigated in many other animals and has implications for behaviors like mate choice and foraging. Our study provides a new perspective into the ecology of Indian FRDs and might have implications for companion dogs as well, if they too show this preference.